On unlinkability and denial of service attacks resilience of whistleblower platforms - Phetsouvanh, Silivanxay (2021)
This work explores how to enhance pseudonymous whistleblower submission systems, specifically by supporting protocol level unlinkability, while also making the system resilient against (distributed) denial of service attacks. To that end, we propose a blind signature based protocol which facilitates assignment of trust to anonymous posters in a manner which depends on the quality of prior posts, yet unlinkable to said posts or corresponding poster. This (multi-level) trust is leveraged to prioritize the posts, thus mitigating the effect that spam posts may have on the party reviewing the posts. We design and carry out simulations to explore the resilience of the whistleblower submission system against denial of service attacks while applying the proposed approach. Our experiments affirm that for a range of realistic scenarios the proposed approach provides reasonable mitigation.